Induction of Labour Versus Expectant Management for Large-for-Date Fetuses: A Randomized-Controlled Trial. Issue 2 (June 2016) - Boulvain, M.; Senat, M.V.; Perrotin, F.; Winer, N.; Beucher, G.; Subtil, D.; Bretelle, F.; Azria, E.; Hejaiej, D.; Vendittelli, F.; Capelle, M.; Langer, B.; et al.
Abstract : ( Lancet. 2015;385(9987):2600–2605) As macrosomia is a risk factor for unfavorable delivery outcomes, including operative vaginal or cesarean delivery and shoulder dystocia (with its associated neonatal morbidity), it is important to determine the best clinical practices for the management of pregnancies with large-for-date fetuses. This randomized-controlled trial evaluated the risks and benefits of induction of labor versus expectant management in women with large-for-date fetuses, hypothesizing that induction of labor would prevent shoulder dystocia and other neonatal and maternal morbidity associated with macrosomia, without significantly affecting the risk of cesarean delivery.